2004
DOI: 10.1007/bf02734171
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lipopolysaccharide on consolidation of partial learning in the Y-maze

Abstract: Research on consolidation of long-term memory suggests that acute immune system activation induced by endotoxin lipopolysaccharide (LPS) may disrupt consolidation of newly acquired learning. Adult male Sprague-Dawley rats were trained to perform a simple Y-maze task and were immediately afterwards administered LPS (15 microg/kg) or saline. After a seven-day interval, subjects were returned to the Y-maze and were retrained to criterion. It was found that subjects treated with saline required significantly fewer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…This was proven by Y maze where the percentage spontaneous alternations significantly decreased compared to normal mice. These results are in accordance with a study which showed that the injection of LPS had a disruptive effect on the ability of mice to learn the Y maze [33]. Using the Morris water maze task, LPS-treated mice took a longer time to reach the hidden platform than normal mice.…”
Section: Discussionsupporting
confidence: 91%
“…This was proven by Y maze where the percentage spontaneous alternations significantly decreased compared to normal mice. These results are in accordance with a study which showed that the injection of LPS had a disruptive effect on the ability of mice to learn the Y maze [33]. Using the Morris water maze task, LPS-treated mice took a longer time to reach the hidden platform than normal mice.…”
Section: Discussionsupporting
confidence: 91%
“…2) induced increased expression of pro-inflammatory cytokines in the brain [92][93][94][95] . Circulating LPS and pro-inflammatory cytokines have been shown to disrupt learning and memory in animals [96][97][98][99] , but peripherally administered LPS in IL6-deficient animals did not result in cognitive defects, indicating the probable importance of IL6 in the development of cognitive impairment 100 . IL10 counteracts the production of IL6 by microglial cells 101 , and IL10-deficient animals show increased production of pro-inflammatory cytokines…”
Section: Cytokines and Fatigue Depression And Cognitive Impairmentmentioning
confidence: 99%
“…Substantial data, from a spectrum of clinical settings, highlight links between peripheral inflammation and cognitive symptoms. For example, peripheral activation of the immune system by a subseptic dose of lipopolysaccharide (LPS) has been shown to increase cytokine expression within the brain at levels associated with learning and memory disruption in both models of disease and health . In healthy volunteers, LPS leads to increased levels of IL‐1, TNFα and IL‐6 resulting in impaired working memory and cognitive dysfunction .…”
Section: Neuroinflammation and Cognitive Dysfunctionmentioning
confidence: 99%
“…For example, peripheral activation of the immune system by a subseptic dose of lipopolysaccharide (LPS) has been shown to increase cytokine expression within the brain [96][97][98] at levels associated with learning and memory disruption in both models of disease and health. [99][100][101] In healthy volunteers, LPS leads to increased levels of IL-1, TNFa and IL-6 resulting in impaired working memory and cognitive dysfunction. 102 Similarly, increased peripheral inflammation has also been associated with gradual cognitive decline and the development of dementia in the elderly population.…”
Section: Neuroinflammation and Cognitive Dysfunctionmentioning
confidence: 99%